2021
DOI: 10.48550/arxiv.2103.17264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optoelectronic Properties of Chalcogenide Perovskites by Many-Body Perturbation Theory

Manish Kumar,
Arunima Singh,
Deepika Gill
et al.

Abstract: Chalcogenide perovskites have emerged as non-toxic and stable photovoltaic materials, acting as an alternative to lead halide hybrid perovskites having similar optoelectronic properties. In the present work, we report the electronic and optical properties of chalcogenide perovskites AZrS 3 (A=Ca, Sr, Ba) by using the density functional theory (DFT) and many-body perturbation theory (MBPT viz. G 0 W 0 and BSE). This study includes excitonic analysis for the aforementioned systems. The exciton binding energy (E … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…where coupling constant α quantifies the electron-phonon coupling, m * is the effective mass of electron, m e is the rest mass of the electron, h is Planck's constant, c is the speed of light, ω LO (in [cm −1 ] units) is the optical phonon frequency, 1/ε * is the ionic screening parameter (1/ε * = 1/ε ∞ -1/ε static were, ε static and ε ∞ are static and high frequency dielectric constant) and R y is the Rydberg energy. We have observed that electron-phonon coupling constant of considered RP phases (Table6), are smaller than that of their bulk BaZrS 3 38 . Further, using the extended form of Frohlich's polaron theory, given by Feynman, the effective mass of polaron (m P ) 49 is defined as:…”
Section: S5 In Si)mentioning
confidence: 77%
See 2 more Smart Citations
“…where coupling constant α quantifies the electron-phonon coupling, m * is the effective mass of electron, m e is the rest mass of the electron, h is Planck's constant, c is the speed of light, ω LO (in [cm −1 ] units) is the optical phonon frequency, 1/ε * is the ionic screening parameter (1/ε * = 1/ε ∞ -1/ε static were, ε static and ε ∞ are static and high frequency dielectric constant) and R y is the Rydberg energy. We have observed that electron-phonon coupling constant of considered RP phases (Table6), are smaller than that of their bulk BaZrS 3 38 . Further, using the extended form of Frohlich's polaron theory, given by Feynman, the effective mass of polaron (m P ) 49 is defined as:…”
Section: S5 In Si)mentioning
confidence: 77%
“…It should be noted that in bulk BaZrS 3 ionic contribution to dielectric constant has been observed to be negligible 38 , whereas in RP phases significant role of ionic contribution to dielectric has been observed. 43 .…”
Section: S5 In Si)mentioning
confidence: 94%
See 1 more Smart Citation